Development and evaluation of LAMP-coupled lateral flow device for the detection of MAP in livestock at point of care resource-limited areas - Punati, Rudrama Devi (Braz J Microbiol, 2019)
The Mycobacterium avium subspecies paratuberculosis (MAP) causes paratuberculosis (Johne’s disease), a systemic and chronic inflammation of intestine that affects bovine, small ruminants like goat and sheep. The disease has a greater economic importance in cattle and in small ruminants. But its effective control is impeded due to lack of rapid and accurate diagnostics. The present study is aimed at developing a LAMP-coupled lateral flow device (LFD) for rapid detection of paratuberculosis in livestock animal species such as cattle and in small ruminants at resource-limited areas. LAMP primers with biotin and FITC end tags were designed for IS900 gene specific for MAP. To determine sensitivity of LAMP assay, 10-fold serial dilutions were made from 10 ng/μl MAP stock DNA and were compared with PCR. The detection limits of LAMP-coupled LFD were defined and reactions were repeated for reproducibility. The specificity was evaluated using other infectious bacteria such as M. bovis, M. tuberculosis, Brucella abortus, Leptospira interrogan, Yersinia enterocolitica, Salmonella typhimurium, Listeria monocytogens, and Staphylococcus aureus. A total of 95 samples turned positive for LAMP-coupled LFD out of 389 fecal samples. All the cultural-positive and PCR-positive samples showed positive in LAMP-coupled LFD. Nine samples with negative cultures turned positive in LAMP assay. The overall sensitivity and specificity of the LAMP-coupled LFD assays were 100% and 97.02% respectively in comparison with the culture as the gold standard method. The sensitivity detection limit of developed assay was 10 fg/μl and specificity was 100%. This assay successfully detected MAP not only by using bacterial DNA but also in clinical fecal samples. The clear band formation at control and test positions was observed on LAMP-coupled LFD. The developed assay is a simple, rapid, easy to perform, and is very useful in early diagnosis of Mycobacterium avium subsp. paratuberculosis at point of care resource-limited areas.